'It's our job': Constraints to investigation of atypical disease events—Opinions of Australian veterinarians. (7th May 2021) - Steele, Sandra G.; Mor, Siobhan M.; Toribio, Jenny‐Ann L.M.L.
Abstract: Frontline health practitioners need to be adequately prepared to recognize and respond to atypical disease presentations, some of which may have zoonotic potential. Data from previous research have suggested that veterinarians may face challenges in investigation of disease events due to time and money constraints. As part of an Australia‐wide survey project, veterinarians were asked to answer an open‐ended question regarding potential constraints in investigation of atypical disease events where there may be concern about a zoonosis or emerging infectious disease. Qualitative data were analysed using thematic content analysis with the consideration of the respondent's area of practice and level of experience. Five main themes were identified which encapsulated constraints to disease investigation described by participants, namely: (a) financing of disease investigations, including client willingness/ability to pay in absence of alternative government schemes; (b) client‐related factors, including willingness to consent to investigation and comply with instructions; (c) professional preparedness to act, related to practitioner knowledge and technical competency; (d) workplace environment, impacted by physical, logistical and managerial aspects of workplaces; and (e) access to external technical support, primarily from government veterinary services. Successful investigation and management of atypical diseases, including potential zoonoses, requires preparedness of all veterinarians. Continuing professional education for veterinarians in infection prevention and control and biosecurity, alongside adequate government funding and support will help facilitate optimal health and biosecurity outcomes. Both state and federal governments need to review existing animal health structures to ensure cohesive responses for future disease events.